The effect of a magnetic field and magnetite nanoparticles on the electrodeposition of asphaltenes of a Colombian 21api oil sample. (January 2019) - Roa, M; Molina, D; Correa, R
Abstract: This research focuses on the effect of a magnetic field and magnetic nanoparticles on the electrodeposition of asphaltenes from a Colombian oil sample. Different electrodepositions were carried out by applying an electric field of 100V/cm. Two magnetic field systems were used: a static one and a dynamic one. They both exhibited a magnetic flux density of 0.1mT. Under the absence of fields, we observed a deposit of 7mg on the anode and 8mg on the cathode. However, presence of an electric field deposits increased to 10mg on the anode and to 13mg on the cathode. In the presence of static magnetic field (generated by a transformer), deposits further increased to 26mg and 21mg. When using the dynamic magnetic field (generated by a stator), we obtained deposits of 63mg and 54mg. Subsequently, 1% of magnetite nanoparticles were added to oil. In the absence of fields, deposits remained about the same. With an electric field, we generated deposits of 26mg on the anode and 21mg on the cathode. The transformer-increased electrodeposition to 30mg on the anode and to 24mg on the cathode, while with stator, deposits increased to 114mg and 73mg. Asphaltene deposits were confirmed by spectroscopy.